Music as a tool for foreign language learning in Early Childhood Education and Primary Education. Proposing innovative CLIL Music teaching approaches. - Berta Torras Vila (Universitat Autònoma de Barcelona, 2021)
The present paper aims at promoting pedagogical reflection by providing the theoretical foundations on the connections between foreign language learning (FLL) and music, which shapes a CLIL Music program named MOVIC (Movement & Music in English).  It also encourages the implementation CLIL Music approaches in EFL classrooms. The paper focuses on the benefits that music brings to the English as a Foreign Language (EFL) classroom, as well as it contextualizes the current situation in the Spanish education system and the pedagogical possibilities that the use of music encompasses. Finally, it presents the EFL approach to MOVIC, together with a sample activity, and it provides